ANALYSIS OF SPATIAL DISTRIBUTION AND SERVICEABILITY OF OFFICIAL POLLING STATIONS USING GIS AND WEBGIS IN NABIRE DISTRICT - Prayitno, Gunawan; Majid, Eka Melani (STMIK Sinar Nusantara, 2026)
Temporary waste collection sites play an important role in supporting urban waste management services. However, the spatial distribution and service coverage of official temporary waste collection sites in Nabire District have not been comprehensively evaluated. This study aims to analyze the spatial distribution and service coverage of official temporary waste collection sites using Geographic Information System (GIS) and to implement the results in an interactive WebGIS. A quantitative spatial approach was applied using official TPS point data, landfill location data, administrative boundary data, and GIS-based spatial processing. The analysis included location mapping, Nearest Neighbor Analysis (NNA), 500-meter buffer analysis, dissolve processing, and administrative overlay. The results showed that the distribution pattern of official temporary waste collection sites tends to be clustered, with an NNA value of 0.7636 and a Z-score of -2.02. The 500-meter service coverage reached only 13.14 km² of the 205.26 km² study area, equal to 6.40%, while 93.60% remained outside the service range. The novelty of this study lies in integrating spatial distribution analysis, service coverage evaluation, and WebGIS visualization to support district-scale waste facility planning.